Small Ruminant Piroplasmosis: High Prevalence of Babesia aktasi n. sp. in Goats in Turkiye - Ulucesme, Mehmet Can; Ozubek, Sezayi; Karoglu, Aleyna; Turk, Zeliha Irem; Olmus, Irem; Irehan, Bunyamin; Aktas, Munir (Mdpi, 2023)
Small ruminant piroplasmosis is the hemoparasitic infection of sheep and goats caused by Babesia and Theileria species responsible for clinical infections with high mortality outcomes. The disease is transmitted by ixodid ticks and prevalent in the tropical and subtropical regions of the world, including Turkiye. A prevalence survey, using molecular methods, is conducted in this study to determine the frequency of newly defined Babesia aktasi n. sp. and other tick-borne piroplasm species in small ruminants in Turkiye. A total of 640 blood samples from sheep (n = 137) and goats (n = 503) were analyzed by nested PCR-based reverse line blot (RLB) hybridization. The results show that 32.3% (207/640) of apparently healthy, small ruminants are infected with three Theileria and two Babesia species. Babesia aktasi n. sp. was the most prevalent species in goats, with 22.5% of samples being positive, followed by B. ovis (4%), T. ovis (2.8%), T. annulata (2.6%), and Theileria sp. (0.6%). None of the sheep samples were positive for Babesia aktasi n. sp.; however, 51.8% were infected with T. ovis. In conclusion, the findings reveal that B. aktasi n. sp. is highly prevalent in goats, but absent in sheep. In future studies, experimental infections will determine whether B. aktasi n. sp. is infectious to sheep, as well as its pathogenicity in small ruminants.
Keywords: Babesia aktasi n; sp; small ruminant; PCR-RLB; prevalence